2004
DOI: 10.1074/mcp.m400001-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Intrinsic Proteins in Arabidopsis Plasma Membrane Proteome

Abstract: Identification and characterization of anion channel genes in plants represent a goal for a better understanding of their central role in cell signaling, osmoregulation, nutrition, and metabolism. Though channel activities have been well characterized in plasma membrane by electrophysiology, the corresponding molecular entities are little documented. Indeed, the hydrophobic protein equipment of plant plasma membrane still remains largely unknown, though several proteomic approaches have been reported. To ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
229
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(256 citation statements)
references
References 108 publications
23
229
4
Order By: Relevance
“…and AT3G21189(ATPase 9). Earlier reports have suggested that ATPase8,10 are co-expressed evenly over all vegetative tissues, while ATPase 9 is expressed almost exclusively in pollen [9]. In our data, the 3 form a confected component with 6 peptides, and our analysis showed the relative wild-type expression of the 3 to be 34.3%, 57.5%, 8.22% respectively, confirming this observation.…”
Section: Arabidopsis Itraq Datasupporting
confidence: 90%
“…and AT3G21189(ATPase 9). Earlier reports have suggested that ATPase8,10 are co-expressed evenly over all vegetative tissues, while ATPase 9 is expressed almost exclusively in pollen [9]. In our data, the 3 form a confected component with 6 peptides, and our analysis showed the relative wild-type expression of the 3 to be 34.3%, 57.5%, 8.22% respectively, confirming this observation.…”
Section: Arabidopsis Itraq Datasupporting
confidence: 90%
“…Multiple extractions of purified plasma membranes from Arabidopsis cell suspension cultures with chloroform/ methanol, sodium hydroxide, and Triton X-100 followed by 1-D gel electrophoresis and in-gel tryptic digestion, permitted the identification of 100 plasma membrane proteins by multiple MS analyses. 25 However, only two LRR RLKs were found in that study. Subsequent studies in Arabidopsis using purified plasma membranes from cell suspension cultures incorporated additional enrichment and labeling techniques, which substantially increased the number of LRR RLKs identified.…”
Section: Introductionmentioning
confidence: 66%
“…Using methods, such as differential centrifugation, electrophoresis, or affinity fractionation, cell or tissue lysates are preseparated into fractions containing particular organelles [8,12,14]. After this prefractionation, the "organelle proteome" can be analyzed by use of established proteomics techniques, such as 1-and 2-DE and chromatographic methods followed by MS [8,[12][13][14][15][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…After isolation of organelles or subcellular structures, and before electrophoretic separation and final identification by MS, fractionation by selective extraction with different agents and chromatographic separation with different resins can further facilitate proteome analysis [4,12,[23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%